"Electrolitos, proteínas y transaminasa glútamico pirúviva en vieja azul (Andinoacara rivulatus) y bocachico (Ichthyoelephas humeralis) en ecosistemas lóticos de la Provincia de Los Ríos". - Puente Mendoza, Magaly Monserrate (2020)
The objective of this research was to evaluate the metabolic activity in GPT, electrolytes and proteins in Vieja Azul and Bocachico, captured artisan in the Fumisa, Mocache and Quevedo area, in the Los Ríos province; the experimental design was completely randomized (DCA) with a 2x3 factorial arrangement made up of 6 treatments with 3 repetitions. Factor (A) are the fishing areas and (B) the species for each fishing place, as a reference 30 bocachico and 30 old blue (60 fish per canton), and a total of 180 specimens. Hematological evaluation was performed. Regarding the assessment of blood chemistry, the total protein in the old blue 2.54 g / dL ± 0.54g / dL albumin 2.28g / dL ± 0.51g / dL and the globulin had a value of 0.34g / dL ± 0.13g / dL compared to bocachico in total protein (Pt) 2.80 g / dL ± 0.87g / dL albumin 2.51g / dL ± 0.69 g / dL and in globulins 0.81g / dL ± 0.91 g / dL. Statistical difference was found in terms of place 0.0182 species 0.66185 and place / species interaction 0.0345. Statistical analysis showed significant differences. In the albumin / globulin ratio, the highest percentage was found in Fumisa / old blue with (9.93%) not obtaining a significant difference with the other fishing places. Regarding the GPT in old blue a value of 72 U / L was manifested and in bocachico 326.67 U / L Being not statistically significant for the place 0.0661 while in the species it showed statistical significance 0.0013 and the same for the interaction place / species <0.0001. For electrolytes, calcium it was evidenced that the old blue obtained a value of 2.23 mmol / L ± 0.31 mmol / Being statistically significant for the place 0.0242 for the species 0.0631 there was no statistical difference and in the interaction place / species 0.1142. Key Words: Metabolic activity, anticoagulation, species, blood hematological, labeled.